Effect of hempseed meal on performance, egg quality and egg yolk fatty acids content in laying quails - CUFADAR, Y; GÖÇMEN, R; KANBUR, G; PARLAT, SS (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, the laying performance, external egg quality, egg yolk colour and fatty acids profile of quails (Coturnix coturnix japonica) fed on diets containing hemp seed meal (HSM) were determined. During 8 weeks trial, a total of 150, 10-weeks-old laying quails were used. Five diets were formulated to contain HSM at the level of 0 (control),5, 10, 15, and 20% that represented as 0 HSM, 5 HSM, 10 HSM, 15 HSM and 20 HSM, respectively.The performance parameters were not significantly (P>0.05)influenced by the dietary HSM contents. Eggshell ratio, eggshell breaking strength, egg shape index, egg yolk index and egg yolk colour values were not significantly (P>0.05) influenced by the dietary HSM, whereas eggshell thickness was significantly (P<0.05) affected. The albumen index has been significantly (P<0.05) increased by increasing in the HSM level in the diets. The HSM supplementation to the diets was effective on fatty acid composition and total saturated fatty acids, total mono unsaturated fatty acids and total polyunsaturated fatty acids content of the egg yolk depending on the addition level. In conclusion, HSM can be used to increase egg total monounsaturated fatty acids and especially omega-3 fatty acids without unfavourable effects on the performance and egg quality parameters.